Produção científica sobre a saúde da população ribeirinha no território brasileiro: estudo bibliométrico - Silva, Ricardo Luiz Saldanha da; Santos, Evelyn Rafaela Almeida dos; Andrade, Erlon Gabriel Rego de; Rodrigues, Ivaneide Leal Ataíde; Nogueira, Laura Maria Vidal; Silva, Eliza Paixão da (Revista de Enfermagem da UFSM, 2023)
Objective: to measure scientific production on the riverside population’s health in Brazilian territory. Method: a bibliometric study, with data collected in March and April 2023, using different databases, via the Virtual Health Library, PubMed, Coordination for the Improvement of Higher Education Personnel Journal Portal and the online scientific library. Search strategies were developed with descriptors and keywords. Descriptive statistical analysis was performed, and Bradford’s, Lotka’s and Zipf’s bibliometric laws were applied. Results: the sample consisted of 35 documents, predominantly quantitative original articles, published in English and Portuguese, in from 2019 to 2022. Due to their publication numbers, five authors and four Brazilian institutions were highlighted. Four most influential journals, four most representative keywords and the main terms used in writing the objectives of selected studies were identified. Conclusion: it was evident that scientific production has increased in recent years, but it is necessary to strengthen the volume of studies on the topic.